EVALUATION OF ENVIRONMENTAL FRIENDLY ULTRA LOW IFT SURFACTANTS FOR CHEMICAL EOR APPLICATION - MAHENDRAN, SARVEEN (IRC, 2017)
Throughout the century, Oil & Gas companies have continued to harvest the raw crude oil available readily in underground reservoirs. Various methods have been utilized in the process of effectively recovering crude oil from these reservoirs, such as Enhanced Oil Recovery (EOR). One of the methods for incremental oil recovery in EOR is called surfactant flooding. Though surfactants have proven to be effective in incremental oil recovery, there are implications during the post-flooding process, where the chemicals injected into the reservoir have displayed negative effects towards the surrounding ecosystem. This study aims to evaluate surfactants, that are environmentally friendly and possess Ultra Low IFT reduction capabilities. One surfactant candidate that shows promise in fulfilling the criteria mentioned is Methyl Ester Sulfonate (MES). The surfactant candidate is to undergo three qualitative and quantitative test to evaluate its properties and capabilities for application in a specific offshore field, they are the compatibility & stability test, phase behavior test, and interfacial tension (IFT) test. The results obtained from the 1st stage of testing which is the compatibility & stability test shows that the surfactant has great stability and compatibility with the brine solution of study as there are no visible signs of precipitation formation. The results from the 2nd phase of testing, the phase behavior test, showed that the surfactant solution can react with the crude oil at a proficient level but not at the micro-emulsion state that was required. The results, from the quantitative analysis, IFT test verifies and supports the qualitative data of the phase behavior test that the strength of the MES surfactant is not enough as a single surfactant system to achieve ultra-low IFT state, thus modifications are required to be carried out to the structure of the surfactant and the surfactant should be made into a mixture with other co-surfactants and stabilizers to increase the effectiveness of the surfactant.